RANCANG BANGUN SISTEM KELISTRIKAN WIPER DAN WASHER PADA MOBIL - Pujiono, Akhmad; Setiawan, Sofiyan; Rizqon, Muhamad (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2019)
Wiper and washer electricity is very important for car drivers, because with this electrical system it can reduce the number of accidents, especially during rainy weather. The wiper and washer electrical system is an electrical system that functions to clean the glass from rainwater and dirt that sticks to the windshield. Making the electrical design of the wiper and washer is the same as the electrical system in the car, because all the components in it are the same as those on the car, but this is made into a stand for the purpose of practical media facilities. In the final project, it was carried out to add learning media to support media-based practice with the aim of knowing how the wiper and washer electrical system works, knowing what damage usually occurs to the wiper and washer electrical system, knowing the maintenance carried out for the wiper and washer system. The manufacturing process is carried out in stages by making the frame, followed by the installation of components. After , making the results obtained on the combination switch in the off position above, low speed in the middle position, and high speed in the lower position. And in the high speed position, the results are less than the maximum and the same at the low speed position.Keywords: Wiper and Washer, Body Electrical